Molecular dynamics simulation reveals structural and thermodynamic features of kinase activation by cancer mutations within the epidermal growth factor receptor - Wan, Shunzhou (Journal of computational chemistry, 2011)
Copyright © 2011 Wiley Periodicals, Inc.